Surges and Stops in FDI Flows to Developing Countries : Does the Mode of Entry Make a Difference? - Burger, Martijn J. (World Bank, Washington, DC, 2014)
This paper investigates the factors associated with foreign direct investment "surges" and "stops," defined as sharp increases and decreases, respectively, of gross foreign direct investment inflows to the developing world and differentiated based on whether these events are led by waves in greenfield investments or mergers and acquisitions. Greenfield-led surges and stops occur more frequently than mergers and acquisitions-led ones and different factors are associated with the onset of the two types of events. Global liquidity is the only factor significantly associated with a surge, regardless of its kind, while decline in global economic growth and a surge in the preceding year are the only predictors of a stop. Greenfield-led surges and stops are more likely in low-income and resource-rich countries than elsewhere. Global growth, financial openness, and domestic economic and financial instability enable mergers and acquisitions-led surges. These results differ from those in the literature on surges and stops and are particularly relevant in countries where foreign direct investments dominate capital flows.